The Swedish graduate school in mathematics education – conception, birth and development of a new doctoral programme - Leder, Gilah C.; Brandell, Gerd; Grevholm, Barbro (NOMAD Nordic Studies in Mathematics Education, 2004)
In this paper we trace the establishment of the graduate school in mathematics education in Sweden. To provide a useful context for this initiative we review briefly the evolution of the PhD, the development of doctoral degrees and doctoral programmes in mathematics departments in Sweden, as well as the growing popularity of graduate schools. Progress and programme issues encountered to date are discussed in some detail.